Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
Proceedings of the Fourth Prasasti International Seminar on Linguistics (Prasasti 2018) 2018
DOI: 10.2991/prasasti-18.2018.36
|View full text |Cite
|
Sign up to set email alerts
|

Thai and Indonesian English Students' Problems in Pronouncing English Fricative and Affricate Sounds: A Case Study in IAIN Kediri

Abstract: This study aims to see the phonological problem deviation of English fricative and affricate sound produced by Thai and Indonesian English learners. This sound is interesting to study since the fricative and affricate sounds system among English, Thai and Indonesian are different. Moreover, some English sounds do not exist in the Thai and Indonesian language system. Respondents of this study were Thai and Indonesian students of IAIN Kediri taken purposively since this study is a case study. The result of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…Some phonological aspects in English are absent in Bahasa, such as word stress and several consonant sounds. The finding is in line with many of the previous studies which reveal that the difference of the phonological system between both languages plays a significant role in the student difficulty when learning pronunciation (Donal, 2016;Lestiono and Gusdian, 2017;Gusdian and Lestiono, 2018;Anam, 2018;Sundari, 2018;Andi-Pallawa and Alam, 2013).…”
Section: Student Perception On English Pronunciationsupporting
confidence: 91%
See 1 more Smart Citation
“…Some phonological aspects in English are absent in Bahasa, such as word stress and several consonant sounds. The finding is in line with many of the previous studies which reveal that the difference of the phonological system between both languages plays a significant role in the student difficulty when learning pronunciation (Donal, 2016;Lestiono and Gusdian, 2017;Gusdian and Lestiono, 2018;Anam, 2018;Sundari, 2018;Andi-Pallawa and Alam, 2013).…”
Section: Student Perception On English Pronunciationsupporting
confidence: 91%
“…It has generally been accepted that many Indonesian students still find it a tedious journey to acquire English pronunciation (Donal, 2016;Lestiono and Gusdian, 2017;Gusdian and Lestiono, 2018;Anam, 2018;Sundari, 2018;Andi-Pallawa and Alam, 2013). Such a tenet is plausible to acknowledge as both Bahasa and English do not share comparable phonological and phonetic systems Dardjowidjojo (1978).…”
Section: Introductionmentioning
confidence: 99%
“…The voiceless palato-alveolar fricative [ʃ] does not exist in the Indonesian phonological system as well. Anam (2018) and Sulistyorini & Wibowo (2021) state that due to the sound being not existing in the Indonesian sound system, students did not understand how to pronounce the sounds [ʃ] and therefore, students often substitute the sound to the one seemingly similar or closest in production based on the place of articulation, which is the sound [s].…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Hakim (2012) found that Javanese students tend to put more stress using the sounds [d] and [ ð] when speaking English due to the influence of their Javanese accents. Anam (2018) Lin (2014) found out that EFL Japanese speakers would add some vowels in English words ending with consonant; while Arabic students would insert vowel [I] in an English initial word.…”
Section: Introductionmentioning
confidence: 99%
“…In the impressionistic analysis, /ʃ/ was deemed to have been articulated as [tʃ], like the word "shop" /ʃɒp/ realized as [tʃɒp], suggesting that /tʃ/ and /ʃ/ are problematic sounds for L2 Thai learners. Several research studies (Anam, 2018;Brière & Chiachanpono, 1980;Kitikanan, 2016Kitikanan, , 2017Pansottee, 1992;Richards, 1969;Roengpitya, 2011) have been put forward to address the production or perception of /tʃ/ and /ʃ/ sounds of L2 Thai learners. However, none of them have been conducted to explore the production of /tʃ/ and /ʃ/ sounds by L2 Thai learners by comparing them with the production of the Thai "ช" /tɕʰ/, and focusing on other factors such as vowel contexts and L2 learner's experience.…”
Section: Introductionmentioning
confidence: 99%